Tax Competition for Foreign Direct Investments and the Nature of the Incumbent Firm - Oscar Amerighi; Giuseppe De Feo (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
In this paper we investigate tax/subsidy competition for FDI between countries of different size when a domestic firm is the incumbent in the largest market. We investigate how the nature (public or private) of the incumbent firm affects policy competition between the two governments seeking to attract FDI. We show that the country hosting the incumbent always benefits from FDI if the domestic firm is a public welfare-maximizing firm, while its welfare may decrease when it is a private firm, as already shown by Bjorvatn and Eckel (2006). We also show that, contrary to the case of a private domestic incumbent, a public firm acts as a disciplinary device for the foreign multinational that will always choose the efficient welfare-maximizer location. Finally, an efficiency-enhancing role of policy competition may only arise when the domestic incumbent is a private firm, while tax competition is always wasteful when the incumbent is a public firm.
Keywords: F12; F23; H25; H73; L13; L33; 330; Foreign Direct Investment; Tax/subsidy competition; Public firm; International mixed oligopoly